Prodrugs of E‐selectin Antagonists with Enhanced Pharmacokinetic Properties. (6th December 2021) - Dätwyler, Philipp; Jiang, Xiaohua; Wagner, Beatrice; Varga, Norbert; Mühlethaler, Tobias; Hostettler, Katja; Rabbani, Said; Schwardt, Oliver; Ernst, Beat
Abstract: Because of their large polar surface area, carbohydrates often exhibit insufficient pharmacokinetic properties. Specifically, the carboxylic acid function of the tetrasaccharide sialyl Lewis x, a pharmacophore crucial for the formation of a salt bridge with selectins, prevents oral availability. A common approach is the transfer of carboxylic acid into ester prodrugs. Once the prodrug is either actively or passively absorbed, the active principle is released by hydrolysis. In the present study, ester prodrugs of selectin antagonists with aliphatic promoieties were synthesized and their potential for oral availability was investigated in vitro and in vivo . The addition of lipophilic ester moieties to overcome insufficient lipophilicity improved passive permeation into enterocytes, however at the same time supported efflux back to the small intestines as well as oxidation into non‐hydrolysable metabolites. In summary, our examples demonstrate that different modifications of carbohydrates can result in opposing effects and have to be studied in their entirety. Abstract : Get the whole story : The addition of lipophilic ester moieties to overcome insufficient lipophilicity of selectin antagonists was found to improve passive permeation into enterocytes; however, at the same time it supported efflux back to the small intestines as well as oxidation into non‐hydrolysable metabolites. Our examples demonstrate that prodrug modifications of carbohydrates can result in opposing effects and must therefore be studied in their entirety.